2018
DOI: 10.26682/sjuod.2018.21.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Nephrectomy. A Clinicopathological Study

Abstract: Background: To provide the urologist with the proper histopathological diagnosis of nephrectomy specimens, to correlate the compatibilty of clinical diagnosis and indications of nephrectomy with histopathological results and to see the relative frequency of each type and its specific pathologic characters. The study was conducted at Azadi teaching hospital and in the department of pathology, college of medicine, university of Duhok during a period from (Nov 2012-Nov 2014). A total 161 nephrectomy specimens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…The incidence of oncocytoma in this study was similar to that reported by Vikram Narang et al 2 Incidence of angiomyolipoma was slightly lower than that reported in Abdulghafoor study. 9 Non Neoplastic Diseases: In the present study, the most common indication for nephrectomy was Chronic pyelonephritis similar to Aiman et al, 8 Shaila et al, 12 Popat et al 13 and Abdulghafoor et al 9 There was a slight female predominance similar to Abdulghafoor et al 9 study. Majority of cases were noted in 41-60 age range in contrats to Suryawanshi et al 1 study where majority of cases were in 21-40 age range.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The incidence of oncocytoma in this study was similar to that reported by Vikram Narang et al 2 Incidence of angiomyolipoma was slightly lower than that reported in Abdulghafoor study. 9 Non Neoplastic Diseases: In the present study, the most common indication for nephrectomy was Chronic pyelonephritis similar to Aiman et al, 8 Shaila et al, 12 Popat et al 13 and Abdulghafoor et al 9 There was a slight female predominance similar to Abdulghafoor et al 9 study. Majority of cases were noted in 41-60 age range in contrats to Suryawanshi et al 1 study where majority of cases were in 21-40 age range.…”
Section: Discussionsupporting
confidence: 81%
“…In the present study among the 177 nephrectomy specimens, 36.2% cases were neoplastic conditions and rest 63.8% were non neoplastic conditions. Thus non neoplastic conditions comprised the majority of cases requiring nephrectomy similar to studies done by Ghalayani et al 6 (70.44%), Rafique et al 7 (76.6%), Aiffa Aiman et al 8 (77.2%), Abdulghafoor S et al 9 (72.6%) and Kishor H. Suryawanshi et al 1 (75.76%). However a higher incidence of neoplastic lesions of 52.9% and 58.46% were reported in studies done by Vikram Narang et al 2 and Swarnlata Ajmera et al 10 respectively.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…8 14 cases were seen in males and 20 cases were seen in females giving a male:female ratio of 1:1.4. Female predominance was also seen in Aiman et al 7 (1:2.8), Abdulghfoor et al 9 (1:1.1), Rafique 10 (1:1.5).…”
mentioning
confidence: 52%
“…One case of anaplastic carcinoma (8.3%) ( Figure 7) and one case of high-grade transitional cell carcinoma of renal pelvis (8.3%) ( Figure 7) were encountered ( Table 6). All cases of Wilms tumours ( Figure 8,9) were in patients below the age of 5 years (Table 5).…”
mentioning
confidence: 99%